A QUALITATIVE STUDY ON IMPLEMENTATION OF ORAL AND DENTAL HEALTH SERVICES FOR PREGNANT WOMEN IN PUSKEMAS SUKAMAKMUR BOGOR REGENCY - Tika Puspa Ryanthi; Evi Martha (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2020)
Backgraund: Changes in the oral cavity during pregnancy might affect the fetus. If a pregnant woman suffers from a periodontal infection, she is exposed to low birth weight or premature 19.2 times compared to healthy pregnant women. The effects is as big as smoking or alcohol abuse. This study aims to analyze the quality of the oral and dental health service for pregnant women in Puskesmas Sukamakmur according to PMK No 89 of 2015. Method: The design of the research is a qualitative study, by employing RAP in Puskesmas Sukamakmur Bogor Regency in April 2019. Data collection was conducted by in-depth interviews, secondary data and observation. The informants involved in the research were the Head, Dental Clinic Coordinator, KIA Coordinator, midwives, and pregnant women in the working area of Puskesmas Sukamakmur. Result: The research shows that Puskesmas Sukamakmur is supported by adequate human resources and there is no financial and facilities problem. Dental examination are not included in the SOP for ANC there by pregnant women who are referred are only those with dental problems. Conclusion: Based on the analysis of the result, Puskesmas Sukamakmur is not ready yet to perform oral and dental service for pregnant women. Socialization the importance of dental health in pregnant women has not been evenly distributed. Support is needed from Dinas Kesehatan and also Kementrian Kesehatan should include an oral assessment to the guidelines of ANC.